SLC7A5, SLC7A7, SLC7A8 and TDO2 in basal cell carcinoma. (1st January 2019) - Tina, E.; Prosén, S.; Lennholm, S.; Gasparyan, G.; Lindberg, M.; Göthlin Eremo, A.
Summary: Basal cell carcinoma (BCC) is the most common non‐malignant skin cancer and the number of patients with BCC is increasing worldwide. Despite variations between carcinomas, some tumour‐specific changes can be found across all cases. These changes may include expression of tumour specific factors that could help doctors diagnose a BCC or predict its development, which consequently could lead to the development of new target medicines. In our study, we compared gene expressions in basal cell carcinomas with healthy skin. Gene expression is the process by which specific genes are activated to produce a required protein. Essentially, a cell will express certain genes depending on what the role of the cell will be. The authors of this study used microarray, a method allowing analysis of thousands of genes in one single sample. Among the results they found higher expression of genes involved in transport of amino acids (e.g. SLC7A5, SLC7A7 and SLC7A8) and amino acid metabolism (TDO2) to be of further interest. Tumour cells often depend on altered energy usage and need access to building blocks for growth. When comparing the basal cell carcinomas with healthy skin, the genes SLC7A5, SLC7A8 and TDO2 were significantly upregulated (increased) in the carcinomas. The authors could not prove that there was higher gene expression of SLC7A7. Looking at the cellular origin of the four genes, they found that proteins SLC7A5 and SLC7A8 were expressed by the tumour cells while TDO2 was mainly found in the surrounding tissue and in immune cells. The SLC7A7 protein was located in stratum granulosum, which is a thin layer of cells in the outermost layer of skin called the epidermis. SLC7A7 is not likely involved in carcinogenesis (cancer development). In conclusion, the authors identified several proteins with a potential role in BCC that may be potential targets for special drugs, but further research is needed.